2021
DOI: 10.1021/acs.energyfuels.1c01971
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cerium-Doped CoMoP/MoP@C Heterogeneous Nanorods with High Performance for Overall Water Splitting

Abstract: Doping rare-earth metals or introducing carbon into transition metal phosphides (TMPs) can promote the property and stability of water electrolysis. An original composite nanostructure, cerium-doped and carbon-coated CoMoO4 (Ce-doped CoMoO4@C), was obtained by a simple hydrothermal and annealing process successively. Subsequently, chemical vapor deposition (CVD) was adopted to synthesize carbon-coated and cerium-doped CoMoP/MoP (Ce-doped CoMoP/MoP@C) with diammonium hydrogen phosphate as the phosphorus source.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 47 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…The P 2p spectrum shows the disappearance of the metal phosphide peak and the retention of the PO x peak (133.5 eV). These experimental phenomena are consistent with the established OER mechanism, whereby transition metals and their phosphides form oxyhydroxides in alkaline media. , Under alkaline conditions (1 M KOH), the mechanism of metal oxyhydroxide (MOOH) formation in OER studies is shown in equations as follows …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The P 2p spectrum shows the disappearance of the metal phosphide peak and the retention of the PO x peak (133.5 eV). These experimental phenomena are consistent with the established OER mechanism, whereby transition metals and their phosphides form oxyhydroxides in alkaline media. , Under alkaline conditions (1 M KOH), the mechanism of metal oxyhydroxide (MOOH) formation in OER studies is shown in equations as follows …”
Section: Resultssupporting
confidence: 84%
“…As shown in the further magnified HRTEM images, the distinct lattice fringes with a spacing of 2.13 Å correspond to interplanar distances of the CoMo (111) plane (Figure f1, f2) . Moreover, the lattice spacings of 2.31 and 2.84 Å can be assigned to the (112) and (111) planes of CoMoP (Figure f3,f4), respectively. , The EDS results show the presence of Co, Mo, and P elements (Figure S4), and the proportion of elements is in general agreement with the ICP test results (Table S1). The scanning transmission electron microscopy-high-angle annular dark-field (STEM-HAADF) and the elemental mappings of CoMo/CoMoP/NF show an overall homogeneous distribution of Co, Mo, and P elements across the nanosheet as well as a concentration of Co and Mo elements in the region of the alloy particles (Figure g).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…3g, two peaks seated at 229.2 and 231.5 eV indicate the Mo-P bond, turning out the intense incorporative interaction between Mo and P atoms. Moreover,peaks at 228.3, 232.6, 232.9, and 236 eV are indexed to Mo 4+ and Mo 6+ signals, mainly because of the surface oxidation of MoP originated from high surface energy [40][41][42]. As presented in P 2p region in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Metal molybdates are a family of inorganic materials that have gotten a lot of interest recently because of their widespread use in fields like lithium storage [28], HER [29], hybrid devices [30], luminescence property [31], and heavy metal detection sensors [32]. In particular, MnMoO 4 has received special attention due to its inexpensive cost, exceptional stability, outstanding chemical properties, low toxicity, and abundant oxidation, as well as the original price state of Mo and Mn compared to that of binary transition metal oxides such as FeMoO 4 [33], CuMoO 4 [34], NiMoO 4 [35], CoMoO 4 [36], and others.…”
Section: Introductionmentioning
confidence: 99%